PERAN KOMITE AUDIT DALAM MEMODERASI KONSERVATISME AKUNTANSI TERHADAP CREATIVE ACCOUNTING - Wulandari, Ayu; Machmuddah, Zaky (Dinamika Akuntansi Keuangan dan Perbankan, 2022)
This research was conducted to prove accounting conservatism to creative accounting with GCG as moderating. Property and real estate sub-sector companies in 2018-2019 are the population of this study. Purposive sampling is a research method in selecting samples, resulting in a sample of 30 companies. Data is secondary data obtained through the official website of the Indonesia Stock Exchange (IDX) and data in the form of financial reports. For data processing using Partial Least Square (PLS) application assistance. This study finds evidence that accounting conservatism affects creative accounting, the audit committee plays a role in weakening creative accounting actions when influenced by accounting conservatism, however, the proportion of independent commissioners is unable to moderate accounting conservatism on creative accounting. The implication of this research is the importance of the audit committee as a supervisor in corporate governance and accounting conservatism to minimize creative accounting.